2014
DOI: 10.1111/meca.12055
|View full text |Cite
|
Sign up to set email alerts
|

Raising the Mandatory Retirement Age and its Effect on Long‐run Income and Pay‐as‐you‐go (PAYG) Pensions

Abstract: In this paper we study the effects of raising the mandatory retirement age in the neoclassical growth model context. It is shown that postponement of the retirement age may be harmful for long-run income and even for pensions. Our findings show that the retirement age might be reduced, thereby obtaining a higher income and even higher pension benefits. This suggests that the idea that a higher mandatory age of retirement is always beneficial in the long run for income and pension payments is theoretically cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 33 publications
(51 reference statements)
1
31
0
Order By: Relevance
“…Gruber, Milligan, and Wise () investigated the relation between the labor force participation of the old and the young in 12 OECD countries and showed that the labor participation of the young is not negatively but rather positively associated with that of the old . These empirical results imply that it is worth investigating the case in which old labor and young labor are imperfect substitutes (the elasticity of substitution is finite), as Fanti () himself pointed out in the conclusion (p. 643).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Gruber, Milligan, and Wise () investigated the relation between the labor force participation of the old and the young in 12 OECD countries and showed that the labor participation of the young is not negatively but rather positively associated with that of the old . These empirical results imply that it is worth investigating the case in which old labor and young labor are imperfect substitutes (the elasticity of substitution is finite), as Fanti () himself pointed out in the conclusion (p. 643).…”
Section: Introductionmentioning
confidence: 88%
“…However, is such a conventional view really right? Fanti () theoretically investigated this question using a simple overlapping generations (OG) model, where the old households allocated a part of their endowed time to the labor supply, and demonstrated that raising the mandatory retirement age always reduces capital accumulation and lowers per young income and pension benefit when the capital share is sufficiently high . If this result is valid, such a policy is harmful to both economic growth and fiscal sustainability of the pension system, contrary to the conventional view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another paper that considers retirement (both endogenous and exogenous) and looks at the effects of working longer on welfare is Lachance (2008) that finds that delaying retirement does little to mitigate the negative impact of the expected pension reductions on welfare. Finally, Fanti (2014 and builds an overlapping generations model with pay-as-you-go pensions to study the effects of the postponement of the retirement age and finds that it may be harmful for growth and also for pension payments.…”
Section: Literature Reviewmentioning
confidence: 99%
“… In a macroeconomic analysis, Fanti () uses an OLG model with two overlapping generations where pensions are computed in each period in order to guarantee the equilibrium of the pension system. Interestingly, he shows that, contrary to the common belief, an increase in the minimum retirement age may have, if some conditions are met, a negative macroeconomic effect.…”
mentioning
confidence: 99%